STEM to story enthralling and effective lesson plans for grades 5-8 - Traig, Jennifer (Jossey-Bass, 2015)
"Bring STEM to life for students with zombies, rockets, celebrities, and more STEM to Story: Enthralling and Effective Lesson Plans for Grades 5-8 inspires learning through fun, engaging, and meaningful lesson plans that fuse hands-on discovery in science, technology, engineering, and math (STEM) with creative writing. The workshop activities within the book are the innovative result of a partnership between 826 National's proven creative writing model and Time Warner Cable's Connect a Million Minds, an initiative dedicated to connecting young people to the wonders of STEM through hands-on learning. Authentically aligned with both the Common Core State Standards and the Next Generation Science Standards, this book provides teachers, after-school and out-of-school providers, and parents with field-tested lessons, workshops, and projects designed by professionals in each field. Including reflective observations by arts and science celebrities like Jon Scieszka, Mayim Bialik, and Steve Hockensmith, lessons feature bonus activities, fun facts, and teaching points for instructors at every level. These quirky, exploratory lessons will effectively awaken student imaginations and passions for both STEM and creative writing, encourage identity with scientific endeavors, and make both science and writing fun. Grades five through eight is the critical period for engaging students in STEM, and this book is designed specifically to appeal to - and engage - this age group. The guided curricula fosters hands-on discovery, deep learning, and rich inquiry skills while feeling more like play than school, and has proven popular and effective with both students and teachers. Awaken student imagination and get them excited about STEM Fuse creative writing with STEM using hands-on activities Make scientific principles relevant to students' lives Inspire students to explore STEM topics further The demand for STEM workers is closely linked to global competitiveness, and a successful future in STEM depends upon an early introduction to the scientific mindset. The challenge for teachers is to break through students' preconceptions of STEM fields as "hard" or "boring," to show them that STEM is everywhere, it's relevant, and it's loads of fun. For proven lesson plans with just a dash of weird, STEM to Story is a dynamic resource, adaptable and applicable in school, after school, and at home"--Provided by publisher.